Analysis of Archival Management in Improving the Quality of Dynamic Archive Management at the Supreme Audit Agency of the Republic of Indonesia (BPK RI) Representative of Bali Province - Amalia, Risa; Yudharta, I Putu Dharmanu (Westscience Press, 2024)
Every government and private organization is always related to administrative activities that produce important documents which, these documents will become archives and must be managed with good archival management. The purpose of this study was to determine the implementation of archival management in improving the quality of dynamic archive management at the BPK RI Office of Bali Province Representative. Archival management is a series of work processes that include recording, controlling, distributing, storing, monitoring, maintaining, moving / shrinking, and destroying. Qualitative research with a descriptive approach is the method used in this research. The research findings conclude that archival management at the BPK RI Office of Bali Province Representative has been well implemented. This can be seen from the implementation and fulfillment of all archival management indicators at the BPK RI Representative of Bali Province. Although there are still some shortcomings, these can still be improved and perfected. Recommendations that can be given for archival management at BPK RI Representative of Bali Province are optimizing the use of technology, expanding the archive room, and adding Human Resources (HR) in the field of archives. The update in this study compared to previous studies lies in the research location and the object of research which focuses on dynamic archives.